Estimating the Effect of Racial Discrimination on First Job Wage Offers - Eckstein, Zvi; Wolpin, Kenneth I. (The Review of Economics and Statistics, 1999)
In this paper we develop and implement a method for bounding the extent to which labor market discrimination can account for racial wage differentials. The method is based on a two-sided, search-matching model that formally accounts for unobserved heterogeneity and unobserved offered wages. We find that racial differences in offered wages are proportionately twice (three times) as large as racial differences in accepted wages for high-school dropouts (high-school graduates). The results indicate that discrimination could account for the entire racial wage-offer differential for high-school dropouts and for high-school graduates, i.e., the bound on the extent of discrimination is not informative.